The Development of Android Application Media Based on PQ4R Learning Strategy on Cognitive Learning Result of Class X Students on Ecosystem Materials (Journal of Biology Education, 2023)
The purpose of this research is to analyze the feasibility of the android application media based on PQ4R learning strategy according to experts and users and to find out the effectiveness of the media on the cognitive learning result of class X MIPA SMA Negeri 1 Batang on ecosystem material. This type of research is Research and Development (R & D) with research procedures using the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques using observation, interview, questionnaire, and test. The results showed that the percentage obtained from material experts, media experts, and users, namely teachers and students with very decent criteria. The results of the study showed that there was a significant increase in cognitive learning result after using the android application media based on the PQ4R learning strategy on ecosystem material in class X MIPA SMA Negeri 1 Batang which was proven by the results of hypothesis test with Fcount (16,094) > Ftable (3,93). It is also proven in the results of the average posttest score of 87.81 compared to the average pretest value of 47.20 with an N-Gain of 0.77 in the high criteria. This study concludes that the android application media based on the PQ4R learning strategy on ecosystem material was declared very feasible by material experts, media experts, and users, namely teachers and students to use in learning and effectively improve student cognitive learning result.